Reflexiones sobre la regulación de la eutanasia, el derecho a la vida y a la dignidad: el caso Ana Estrada, Perú - Pulido Del Pino, Natali Juliana (2023)
Objective: The purpose of this article is to analyze the concept of euthanasia and its relationship with the rights to life and dignity, as well as the evolution of its legalization in the different legal systems of the world and, especially, in Peru, in the context of the recent award issued by the Supreme Court, on July 27, 2022, regarding the Ana Estrada’s Case. Method: The methodological approach is a qualitative research. It is a doctrinal research, based on human rights, constitutional law, comparative law, and alludes to the jurisprudence on the subject at a national and international level. Results: The results allude to the rights to free disposition of the body, to life and to human dignity, as axes to make assisted death possible. This is a doctrinal research based on human rights, constitutional law, comparative law, and alludes to the jurisprudence on the subject at the national and international level. The relevance of this article relies on comparing how it has been the inclusion of euthanasia to the legal framework in the different legal systems until reaching the Peruvian one. Conclusions: The contribution made, evidences the recognition of the legality of euthanasia in the different legal systems, as well as values in Peruvian law, the impact of the issued award that has recognized for the first time, in its history, the right to a dignified death, which is already a milestone on which we must continue to analize.